Miejska gospodarka o obiegu zamkniętym - Sobol, Agnieszka (Public participation in urban climate policy making: The example of Lodz, 2024)
One of the strategic directions of the development of modern cities is a circular economy (CE). The circular economy is a way of conducting social and economic processes oriented towards resource efficiency and minimization of waste production. Its effect is low-carbon emissions contributing to building climate neutrality. The complex approach to the development of the circular economy includes responsible and economical management of resources and their repeated use in the process of exchange or change of use. The multifaceted approach requires linking technological and organizational changes with economic and social impact mechanisms as well as continuous ecological education. The key area of circular economy is the partnership and cooperation of many local entities. An import- ant role in coordinating the development of the urban circular economy is played by local governments, which should actively and on an ongoing basis initiate, support and promote activities for its development. At the same time, these are the inhabitants who are the real agents of change toward the circular economy. Ultimately, it is their awareness and attitudes that contribute to its realization.